REQUEST AND PERMISSION: MAKING POLITE REQUESTS, ASKING, RESPONDING, AND REFUSING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article investigates the linguistic and pragmatic aspects of making polite requestsand asking for permission in English. It explores how speech act theory and politeness strategies contribute to effective communication. The paper also analyzes various forms of asking, responding, and refusing, with emphasis on cross-cultural aspects and their implications for language learners and educators.